Design and development of a five-bar robot for research into lower extremity proprioception - Cui, L.; Isaac, A.; Allison, Garry (Cambridge University Press, 2017)
Ankle inversion is a common injury of musculoskeletal system among athletes and also in the older population. Investigation into ankle inversion requires quantitative assessment of the smallest amount of height/angle change in the floor that can be perceived by human. Blocks of different thickness have been used to change floor height manually during tests. We aimed to develop an automatic apparatus that is able to provide improved height and angle resolutions for dynamic ankle proprioception. We designed and manufactured a five-bar planar robot with one coupler serving as the mobile platform. We used a stiffening rib to achieve consistent differences in deflection across the workspace of the mobile platform. The reported robot translates at the maximal speed 423 mm/s with a resolution at 0.21 mm under a maximal load of 358 kg. This robot allows for increased sensitivity, which may lead to further investigation of functional proprioceptive ability and reflect finely tuned sensory requirements for upright stance.